2014
DOI: 10.1002/bin.1395
|View full text |Cite
|
Sign up to set email alerts
|

Using Calibration and Interobserver Agreement Algorithms to Assess the Accuracy and Precision of Data From Electronic and Pen‐and‐paper Continuous Recording Methods

Abstract: Often it is assumed that electronic recording by observers necessarily provides better quality data than pen-and-paper methods. Fifteen novice observers recorded rates of responding from 10 role-played video samples using one of three continuous recording input formats: keyboard (laptop), touchscreen (personal digital assistants), or pen-and-paper. We evaluated the quality of the observers' data compared with criterion records using calibration and interobserver agreement algorithms. Results of the calibration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
4
2
Order By: Relevance
“…Our findings differed from those of Phillips et al. (2014), where the touchscreen condition was more accurate and precise than pen‐and‐paper for one participant. This discrepancy may be a function of the observation systems in each study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our findings differed from those of Phillips et al. (2014), where the touchscreen condition was more accurate and precise than pen‐and‐paper for one participant. This discrepancy may be a function of the observation systems in each study.…”
Section: Discussioncontrasting
confidence: 99%
“…Electronic data collection (EDC) has the potential to address many limitations of pen‐and‐paper recording (Phillips et al., 2014). Copies of data may be produced instantly and with limited environmental impact.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phillips et al (2014) conducted a study with 15 observers recording response rates from 10 video clips using one out of three input formats: keyboard (laptop), touch screen (digital assistants personal), or paper-and-pencil. The results showed that although the electronic record had the potential to be more accurate and more reliable than paper-and-pencil method, this was far from being conclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Internet‐connected cameras allow professionals to obtain extended recordings of caregiver–client interactions in natural settings, and hand‐held computers, tablets, and smartphones have made continuous measurement easier to conduct (Phillips et al, 2014). However, it is impractical to score extended observations at normal speed to measure instances of low‐rate behavior.…”
mentioning
confidence: 99%